INDUSTRIAL APPROACH OF JAPAN: A POSSIBLE MODEL FOR BALANCED REINDUSTRIALIZATION AND REGIONAL DEVELOPMENT OF BULGARIA IN THE NEXT PROGRAMMING PERIOD: 2028-2035 (TRAKIA JOURNAL OF SCIENCES, 2025)
The goal of this study is to suggest a model how to integrate industrial advantages of Japan with Bulgaria’s EU Perspectives in the next programming period: 2028-2035. The authors utilized comparative analytics and critical thinking methods to conceptualize how it is possible to enhance financially sustainable reindustrialization and successful regional development of Bulgaria.The paper sums up the accrued results, based on critical review of industrial relations between Japan and Bulgaria in 70s and 80s and delineates critically important areas of financially balanced and economically sustainable regional development in the forthcoming programming period, streamlined to implement advanced industrial achievements of Japan in Bulgaria.To support the results, the authors provide academic discussion on R&Ds, smart specialization, international economic relations and cooperation for technology transfers, and building international strategic alliances with warranted international financial provisions for production and trade.